O estudo da influência do ciclo de partidas e paradas no estator de geradores síncronos - SANTOS, Renato Lelio da Silva (Universidade Federal do Pará, 2012)
The synchronous generators under different stops situations forced shutdown, shutdown by external conditions, scheduled for corrective and preventive maintenance. The different variations in temperature that undergoes a synchronous generator, exactly to its stator affects its isolation, which does not follow these constant changes, due to have a different coefficient of expansion. In the present work has identified a trend of progressive aging of the insulation of stator windings in their machines that suffer repetitive starting and stopping and staying with his reserve power off for several hours. The study was implemented in five synchronous generators Balbina hydroelectric of Eletrobras group, which presents such a problem. This study confirms for the tests of analysis of partial discharge of the synchronous generators performed periodically to diagnose problems in their stator windings, with different magnitudes and identify the thesis that machines that have larger magnitudes of partial discharges off in their stators are undergoing more amounts of starting and stopping and staying with the most hours with standby power off.